2003
DOI: 10.1046/j.1532-5415.2003.51482.x
|View full text |Cite
|
Sign up to set email alerts
|

Vision and Driving Self‐Restriction in Older Adults

Abstract: Older adults with early changes in spatial vision function and depth perception appear to recognize their limitations and restrict their driving even if they do not acknowledge the visual impairment as the cause for restriction. Poor visual attention, a risk factor for crashes, may not be recognized. Additional studies of driving self-restriction in relation to risk factors for crashes in older adults may help refine this strategy of reducing driving-related injury and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 39 publications
9
42
0
Order By: Relevance
“…As people age, visual functions deteriorate due to increase in the incidence of age-related ocular conditions such as cataract, macular degeneration, open-angle glaucoma, and diabetic retinopathy [6,14,15]. Thus there are 2 accident peaks in the life of an individual, in the young when one is prone to risk taking behaviour and in the elderly when visual impairment prevents adequate visual function.…”
Section: Davidsonmentioning
confidence: 99%
“…As people age, visual functions deteriorate due to increase in the incidence of age-related ocular conditions such as cataract, macular degeneration, open-angle glaucoma, and diabetic retinopathy [6,14,15]. Thus there are 2 accident peaks in the life of an individual, in the young when one is prone to risk taking behaviour and in the elderly when visual impairment prevents adequate visual function.…”
Section: Davidsonmentioning
confidence: 99%
“…So it appears that license restrictions reinforced decisions already made by some drivers. Previous studies have shown that many older drivers limit their driving to situations and environments they perceive as less challenging Charlton, Oxley, Fildes, & Les, 2003;Lyman, McGwin, & Sims, 2001;Stutts, 1998;Vance, Roenker, & Cissell, 2006;West et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…32,40 Although it can be difficult for those with glaucoma who are unaware of the extent of their disease to accept their limitations, 75 research has also found that once aware of visual limitations, drivers will modify their driving habits. 76,77 A major concern for older drivers and in particular, those with glaucoma is losing the ability to drive. 22,61,78 Older drivers who restrict their driving or have surrendered their licenses report increased loneliness, isolation, and higher levels of depressive symptoms [79][80][81][82] resulting in diminished quality of life.…”
Section: Glaucoma Driving Self-regulation and Driving Cessationmentioning
confidence: 99%